2022
DOI: 10.3390/ijms232113210
|View full text |Cite
|
Sign up to set email alerts
|

2.4 GHz Electromagnetic Field Influences the Response of the Circadian Oscillator in the Colorectal Cancer Cell Line DLD1 to miR-34a-Mediated Regulation

Abstract: Radiofrequency electromagnetic fields (RF-EMF) exert pleiotropic effects on biological processes including circadian rhythms. miR-34a is a small non-coding RNA whose expression is modulated by RF-EMF and has the capacity to regulate clock gene expression. However, interference between RF-EMF and miR-34a-mediated regulation of the circadian oscillator has not yet been elucidated. Therefore, the present study was designed to reveal if 24 h exposure to 2.4 GHz RF-EMF influences miR-34a-induced changes in clock ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 140 publications
0
0
0
Order By: Relevance
“…miR-34a administration also inhibited the expression of the clock gene bmal1 and the clock-controlled gene rev-erbα, which agrees with the search performed in miRWalk [66] and previous research [63]. Surprisingly, we observed an elevated level of the clock mRNA concentration after miR-34a administration.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…miR-34a administration also inhibited the expression of the clock gene bmal1 and the clock-controlled gene rev-erbα, which agrees with the search performed in miRWalk [66] and previous research [63]. Surprisingly, we observed an elevated level of the clock mRNA concentration after miR-34a administration.…”
Section: Plos Onesupporting
confidence: 92%
“…administration of mimic miR-34a together with an inhibitor caused an increase in per2 expression. The same effect has been observed without regard to whether mature miR-34a or pre-miRNA was administered to the DLD1 cell culture [63].…”
Section: Plos Onesupporting
confidence: 67%
“…Studies that indicated miR-34a as a tumour suppressor have been criticised for the use of supra-physiological levels of synthetic mimics [48], and the off-target activity of miR-34a has been demonstrated recently [37]. We have also observed the effect of a high-frequency electromagnetic field (RF-EMF) on the oncostatic functions of miR-34a [36].…”
Section: Functions Of Small Non-coding Rnas and Their Modulation By E...mentioning
confidence: 78%
“…An altered functionality of miR-34a in the colorectal cancer cell line DLD1 exposed to EMF with 2.4 GHz frequency (RF-EMF) was demonstrated by our group [36]. The exposure of DLD1 cells to RF-EMF potentiates the capacity of miR-34a to induce the expression of the clock gene cry1 that was not observed under control conditions.…”
Section: Interference Of An Electromagnetic Field On Mir-34-mediated ...mentioning
confidence: 85%
See 1 more Smart Citation